Chronic cerebrovascular abnormalities in a mouse model of repetitive mild traumatic brain injury. (14th October 2016) - Lynch, Cillian E.; Crynen, Gogce; Ferguson, Scott; Mouzon, Benoit; Paris, Daniel; Ojo, Joseph; Leary, Paige; Crawford, Fiona; Bachmeier, Corbin
Abstract: Primary objective : To investigate the status of the cerebrovasculature following repetitive mild traumatic brain injury (r-mTBI). Research design : TBI is a risk factor for development of various neurodegenerative disorders. A common feature of neurodegenerative disease is cerebrovascular dysfunction which includes alterations in cerebral blood flow (CBF). TBI can result in transient reductions in CBF, with severe injuries often accompanied by varying degrees of vascular pathology post-mortem. However, at this stage, few studies have investigated the cerebrovasculature at chronic time points following repetitive mild brain trauma. Methods and procedures : r-mTBI was delivered to wild-type mice (12 months old) twice per week for 3 months and tested for spatial memory deficits (Barnes Maze task) at 1 and 6 months post-injury. At 7 months post-injury CBF was assessed via Laser Doppler Imaging and, following euthanasia, the brain was probed for markers of cerebrovascular dysfunction and inflammation. Main outcomes and results : Memory impairment was identified at 1 month post-injury and persisted as late as 6 months post-injury. Furthermore, significant immunopathological insult, reductions in global CBF and down-regulation of cerebrovascular-associated markers were observed. Conclusions : These results demonstrate impaired cognitive behaviour alongside chronic cerebrovascular dysfunction in a mouse model of repetitive mild brain trauma.